A4.10 The comparison of osteoclastogenic potential of blood and bone marrow plasma from rheumatoid arthritis (RA) and osteoarthritis (OA) patients. (24th February 2016) - Radzikowska, A; Plebanczyk, M; Kurowska, W; Burakowski, T; Nowakowska-Plaza, A; Gasik, R; Gluszko, P; Maslinski, W
Abstract : Background and objectives: Alterations of OPG/RANKL ratio are critical in bone pathology in RA. Therefore the aim of this study was to investigate the osteoclastogenic potential of RA and OA blood and bone marrow plasma. Materials and methods: Bone marrow samples were obtained during routine total hip replacement surgery. Levels of soluble RANKL, osteoprotegerin (OPG) and sclerostin in plasma were evaluated by ELISA. To compare the osteoclastogenic potential of RA and OA blood and bone marrow plasma, adherent PBMCs isolated from healthy blood donors were cultured for 15–21 days in the presence of heat inactivated plasma. Osteoclasts (OCs) differentiation was examined by TRAP staining and calcified matrix resorption activity. Results: Significantly higher levels of soluble RANKL in blood and bone marrow plasma from RA than from OA were observed, which correlated with disease activity. OPG levels were comparable between RA and OA. A tendency to higher osteoclastogenic potential of RA blood plasma was reflected by stronger resorptive activity of osteoclasts in comparison to OA. Interestingly, RA blood plasma promoted enhanced differentiation of monocytes into large osteoclasts (≥10 nuclei), whereas OA plasma induced mainly small osteoclasts (less than 10 nuclei). This phenomenon was not observed for bone marrow plasma. Both RA and OA bone marrow plasma stimulated differentiation of osteoclasts. The osteoclastogenic potential was comparable between OA and RA, despite higher level of soluble RANKL in RA bone marrow plasma. Bone marrow soluble RANKL may originate from membrane form shed during inflammation, as monocytes and T-lymphocytes exert significantly lower RANKL surface expression. Sclerostin concentrations in OA, but not RA, bone marrow plasma correlated with resorption activity of OCs. Conclusions: RA blood plasma has stronger osteoclastogenic property than OA. Bone marrow plasma promotes osteoclastogenesis without significant differences between RA and OA.